Warming Events Advance or Delay Spring Phenology by Affecting Bud Dormancy Depth in Trees - Malyshev, Andrey V. (Frontiers in Plant Science, 2020)
The frequency of sudden, strong warming events is projected to increase in the future. The effects of such events on spring phenology of trees might depend on their timing because spring warming has generally been shown to advance spring budburst while fall and winter warming have been shown to delay spring phenology. To understand the mechanism behind timing-specific warming effects on spring phenology, I simulated warming events during fall, mid-winter and at the end of winter and quantified their effects on bud dormancy depth and subsequently on spring leaf out. The warming events were carried out in climate chambers on tree saplings of Betula pendula and Fagus sylvatica in October, January and February. Control saplings were kept at photoperiod and temperature matching the daily fluctuating field conditions. Warmed saplings were kept 10°C warmer than the control saplings for ten days during the respective warming periods. Warming in October increased bud dormancy depth and decreased spring leaf-out rate only for F. sylvatica, whereas warming in February reduced bud dormancy depth and advanced spring leaf-out rate only for B. pendula. Neither bud dormancy depth nor spring leaf out rate were affected by January warming. The results indicate that warming-induced changes in bud dormancy depth may explain species- and timing-specific warming effects on spring phenology. The extent to which the timing of bud dormancy phases is species-specific will influence among-species variation in future spring leaf out times.